SELF-EDUCATION AS AN INDIVIDUAL SELF-ORGANIZATION: PHILOSOPHICAL - EDUCATIONAL ASPECT - Chaika, Yana (Global Prosperity, 2021)
In the modern age of civilisation, there are significant transformations in various spheres of public life. This is especially true of modern education, which has found itself at the crossroads of various waves, currents, on the verge of contradictions, both of a general nature and in conditions of information and spiritual uncertainty. The main contradiction of the modern socio-cultural era was clearly manifested - between the diverse world of information, knowledge, spiritual and value guidelines, and the realisation of the individual who is learning in terms of its place in the modern world. First of all, it is a system of challenges from the point of view of the global information society, in which a young person is in a state of confusion. Secondly, most people who study are forced to study remotely in a prolonged pandemic because they lose the main source of successful education - the state of direct communication with the teacher, in general, with the education system. This is especially true for children, adolescents and young adults. For these people, almost the only source of education is electronic virtual systems, which require special skills and abilities. The philosophy of education as a methodology of modern educational processes aims to develop certain theoretical and practical approaches to the direction of the individual on the path of self-education, which is becoming the main socio-cultural trend